Management of Failing Coils During Embolization of Intracranial Aneurysms: A Case Report and a Review of the Literature - Ge, Yuanhong; Lai, Qingjia; Xu, Xuejun (Journal of endovascular resuscitation and trauma management, 2024)
Coils failing through processes such as unraveling, fracturing, and distal migration are rare during embolization of intracranial aneurysm, but these intraoperative complications might lead to serious consequences. Although several rescue techniques have been reported, the standard technique remains unclear. Herein, we report a case pertaining to removing a failing coil by a simple and economical measure. Literature on the concerned topic was also reviewed. Based on the literature, rescue techniques are classified into two types: removing the failing coils; and keeping the failing coils steady in the blood vessel by applying some appropriate measures. The former type consists of twisting, gripping, aspiration, and wedging techniques, whereas the latter includes stent-compressed techniques and end-fixing techniques.